Neonatal exposure to sevoflurane induces adolescent neurobehavioral dysfunction by interfering with hippocampal glycerophoslipid metabolism in rats. (19th May 2022) - Wang, Yonghai; Li, Hongchun; Zhao, Ying; Qin, Feng; Wang, Liang; Jiang, Linhong; Wang, Xiaojie; Chen, Rong; He, Yuman; Wei, Qinfan; Li, Shu; Chen, Yuanyuan; et al.
Abstract: Sevoflurane exposure in the neonatal period causes long-term developmental neuropsychological dysfunction, including memory impairment and anxiety-like behaviors. However, the molecular mechanisms underlying such effects have not been fully elucidated. In this study, we investigated the effect of neonatal exposure to sevoflurane on neurobehavioral profiles in adolescent rats, and applied an integrated approach of lipidomics and proteomics to investigate the molecular network implicated in neurobehavioral dysfunction. We found that neonatal exposure to sevoflurane caused cognitive impairment and social behavior deficits in adolescent rats. Lipidomics analyses revealed that sevoflurane significantly remodeled hippocampal lipid metabolism, including lysophatidylcholine (LPC) metabolism, phospholipid carbon chain length and carbon chain saturation. Through a combined proteomics analysis, we found that neonatal exposure to sevoflurane significantly downregulated the expression of lysophosphatidylcholine acyltransferase 1 (LPCAT1), a key enzyme in the regulation of phospholipid metabolism, in the hippocampus of adolescent rats. Importantly, hippocampal LPCAT1 overexpression restored the dysregulated glycerophospholipid (GP) metabolism and alleviated the learning and memory deficits caused by sevoflurane. Collectively, our evidence that neonatal exposure to sevoflurane downregulates LPCAT1 expression and dysregulates GP metabolism in the hippocampus, which may contribute to the neurobehavioral dysfunction in the adolescent rats.